2019
DOI: 10.1002/tox.22864
|View full text |Cite
|
Sign up to set email alerts
|

Total flavonoids of Epimedium ameliorates testicular damage in streptozotocin‐induced diabetic rats by suppressing inflammation and oxidative stress

Abstract: Testicular damage is the anomaly that will often accompany diabetes mellitus. Thus, this study aimed to investigate the role that total flavonoids of Epimedium (TFE) played against streptozotocin (STZ)‐induced diabetic testicular dysfunction and to elucidate the mechanism of action. The diabetic rat model was induced by vein injection of STZ in healthy rats. Thirty male healthy Spraque‐Dawley rats were randomly divided into following groups: the control group, the diabetic group, and the diabetic + TFE group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Testicular damage caused by diabetes can result in the loss of testicular activities of certain marker of spermatogenesis, including ACP and LDH 10,34,35 . It was observed that ACP and LDH in the testes of the diabetic rats were significantly decreased and SRE was able to significantly ameliorate these alterations by increasing the levels of these enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Testicular damage caused by diabetes can result in the loss of testicular activities of certain marker of spermatogenesis, including ACP and LDH 10,34,35 . It was observed that ACP and LDH in the testes of the diabetic rats were significantly decreased and SRE was able to significantly ameliorate these alterations by increasing the levels of these enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes induced reproductive dysfunction occurs in about 35% to 90% of diabetic patients 5‐7 . In males the evidence of diabetic induced sexual and testicular dysfunction includes hypotestosteronaemia, abnormal spermatogenesis, reduced libido and ejaculatory dysfunction 8‐10 …”
Section: Introductionmentioning
confidence: 99%
“…The main chemical constituents of the Rhizoma drynariae extract include phenolic acids, flavonoids and triterpenes, as well as their glycosides (8). Among these, studies have mainly focused on total flavonoids (23)(24)(25). As TFRD has antioxidant properties and anti-osteoporosis activity, it has been widely used in clinic and has great value in research and development (26).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation and oxidative stress are two major factors contributing to diabetes-induced injuries [43,44]. And inhibition of inflammation and oxidative stress develop protective effects in diabetes [45][46][47][48]. Cyclophilin A is confirmed to be secreted by cells under the stimulation of inflammation and oxidative stress [49].…”
Section: Discussionmentioning
confidence: 99%